Pengaruh Foto Produk terhadap Minat Beli Konsumen pada Akun Instagram @skintificid - Arimiawati, Intan; Moenawar, Mohamad Ghozali; Suparman, Suparman; Muhammad, Badar; Manisya, Nabhila; Awalina, Salwa Putri (Penerbit Goodwood, 2024)
Purpose: This study analyzes the influence of product photos on consumers’ interest in the Instagram account @skintificid, targeting its followers.Methodology: A quantitative approach was employed utilizing online questionnaires distributed via Google Forms. The sample size was determined using the Slovin formula with a sampling error of 10 %.Results: The study found a significant but weak negative correlation between product photos and consumers’ purchasing interest. This indicates that, as the quality of product photos increases, purchasing interest decreases. Therefore, while the hypothesis that product photos influence consumer interest is accepted, this influence is negative.Conclusions: The study shows that Skintific is more popular among young women with limited purchasing power. Attractive product photos can encourage purchases, but unrealistic expectations may lower interest. Purchase decisions are influenced by visual elements, preferences, reviews, and purchasing power.Limitations: The research focuses solely on skincare brands, limiting its generalizability. Additionally, the sample consisted exclusively of female respondents, which may not accurately represent a broader consumer base.Contribution: The findings contribute to the understanding of how product imagery affects consumer buying interest, particularly in the context of social media marketing.